Tahap Perkembangan Karakter Utama Dalam Novel Ayahku Bukan Pembohong Karya Tere Liye: Kajian Teori Jean Piaget - Uhti Lestari; Tisyani Tisyani; Eva Dwi Kurniawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the stages of development of the relationship between fathers and their children according to Jean Piaget's theory in the novel entitled My Father is Not a Liar by Tere Liye. This study used descriptive qualitative method. Analysis of the developmental stages of the relationship between father and son in the novel Ayahku Is Not a Liar using a literary psychology approach. Development is a pattern of change that begins at conception and continues throughout a human's lifetime. Most development involves growth, although it also includes decline caused by the processes of aging and death. The analysis used is the theory of cognitive development by Jean Piaget. The problem of this research is how the character of children begins to understand the meaning and understanding of life. The results of the analysis of the novel Ayahku Is Not a Liar can be concluded that there is strong emotional and intellectual development in the main character through the process of disclosure and understanding. through the process of disclosure and understanding, their relationship gradually improves and becomes more harmonious. This shows the importance of communication and understanding in building healthy family relationships